Student’s Interest in Writing Transactional Text by Using Origami Paper at MTs PP Darul Qur’an - Sofia Listika; Muhammad Taufik Ihsan (TRANSFORM: Journal of English Language Teaching and Learning, 2024)
Using origami paper become one of the effective ways to teach writing. In fact, each student has different interests in writing and the use of origami paper in increasing student interest is still considered unclear. This study is designed to describe student’s level of interest and the dominant indicator of students’ interest in writing transactional text by using origami paper. The design of this research was descriptive quantitative research and the researcher uses a survey model. The population of this study was second year students at MTs PP Darul Qur’an and the sample of this research was taken by using total sampling was 60 students. The techniques of collecting data were close-ended questionnaire. Based on the analysis of student’s interest in writing transactional text by using origami paper, shows that the total score was 5059 with the percentage 84%. It means that the category of student’s interest in writing transactional text by using origami paper is very high level. The researcher also found that the enjoyment indicator was the most dominant indicator of students' interest.